The enforceability of non-disclosure and non-compete clauses in the fintech sector within the European Union - Ruks, Reinis (Riga Graduate School of Law, 2023)
Non-compete agreements, non-disclosure agreements, and other types of restrictive covenants are becoming increasingly popular in many business areas worldwide. Some scholars and professionals argue that restrictive covenants negatively impact innovation and entrepreneurship, while others believe that these types of agreements are essential for protecting proprietary and confidential information. Whilst it can be argued that both sides of the argument have valid facts to support their claim, countries such as the United States are rethinking whether or not to ban non-compete and non-disclosure agreements altogether. This is a topical question also within the European Union. In the EU, the law governing trade secrets is the national civil law of each country. Even though the European Union has approved the European Union Trade Secrets Directive, this is seen more as a guideline for drafting legally binding documents rather than a set of laws that govern restrictive covenants. Perhaps a unified system of legislation would be helpful to organize the system of trade secret regulation and restrictive covenants in employee contracts, however, at this point, there is a large deal of variation between different jurisdictions applying different laws. The enforceability of non-compete and non-disclosure clauses in employee contracts is directly affected by the disparity of the regulation and it is important both for employers and employees to know and understand the applicable laws.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Competition law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; FinTech